IMPLEMENTASI PROGRAM KELUARGA HARAPAN PERLINDUNGAN LANJUT USIA (PKH PLUS) DI KECAMATAN PAMEKASAN KABUPATEN PAMEKASAN - Oktavia Brianita; Ananta Prathama (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2024)
The aging of the population and problems with the welfare of the elderly cannot be separated from Pamekasan Regency as one of the districts with extreme poverty levels in East Java. To realize East Java Provincial Regulation Number 5 of 2007 concerning Elderly Welfare, the first Nawa Bahkti Satya Governor and Deputy Governor of East Java, namely Jatim Sejahterah, was drafted, namely Jatim Sejahterah, which aims to support the realization of planned, directed and sustainable elderly welfare in the form of a Provincial Regional Regulation. East Java. The Family Hope Program Elderly Protection, hereafter in this research, is called (PKH Plus). This research uses a qualitative descriptive research type. Theoretical analysis uses the George C Edward III implementation model. The results of this research show that PKH Plus has been implemented in Pamekasan District, Pamekasan Regency. In its implementation, the Pamekasan Regency Social Service as the district level PKH Plus implementer is assisted by PKH coordinators and assistants to disseminate information, implement programs, and monitor and evaluate the implementation of PKH Plus in Pamekasan District, Pamekasan. Area. Obstacles in implementing PKH Plus are the existence of data on elderly people in the DTKS that is not appropriate, inconsistent implementation techniques, uneven distribution of accompanying tasks, and inadequate facilities. Optimization needs to be done so that poor elderly people can receive assistance evenly.